Combined UMBAF-MBAF process treating detergent wastewater - Ji, Guixia; Zhou, Yanhong; Zhou, Buxuan; Yun, Yunbo; Chen, Zhongbing; Liu, Hongbo (Water environment research, 2019)
A combined process of the upflow multimedium biological aerated filter (UMBAF) and the multimedia biological aerated filter (MBAF) treating detergent wastewater was investigated in this study. Results showed that the optimal filtration rate of the combined system was 1.4 m/hr while the optimized performance was observed at air to water ratio of 2:1. The average removal rate of chemical oxygen demand (COD), linear alkyl benzene sulfonate sodium (LAS), and total phosphate (TP) was up to 91.4%, 88.5%, and 40%, respectively, while the average effluent concentrations of COD, LAS, and TP under stable operation states were 35.0 mg/L, 7.0 mg/L, and 4.4 mg/L, respectively. UMBAF played a major role in TP removal; the removal of COD in the combined UMBAF and MBAF process was consistent with the general formula C = C0 e -(ah + b) , while the kinetic model of LAS removal in the combined UMBAF and MBAF process could be expressed by L = L0 e-(mh + n) . The combined UMBAF-MBAF process provides a promising technology for the treatment of detergent wastewater. The kinetic model of LAS removal in the UMBAF and MBAF units is helpful for the prediction of the treatment efficiency of organic pollutants. PRACTITIONER POINTS: A novel UMBAF-MBAF process was developed treating detergent wastewater. The average removal rate of COD, LAS, and TP by the combined process was up to 91.4%, 88.5%, and 40%, respectively. Kinetic models for the UMBAF-MBAF process were investigated.
Keywords: multi-filter; detergent wastewater; chemické modely; Alkanesulfonic Acids; čištění vody; Wastewater; Kinetics; Waste Water; Water Purification; Models, Chemical; detergenty; combined UMBAF-MBAF; Bioreactors; fosfáty; odpadní voda; filtration rate; Detergents; bioreaktory; degradation model; kinetika; kyseliny alkansulfonové; Phosphates